2018
DOI: 10.1016/j.physa.2017.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Microcanonical entropy for classical systems

Abstract: The entropy definition in the microcanonical ensemble is revisited. We propose a novel definition for the microcanonical entropy that resolve the debate on the correct definition of the microcanonical entropy. In particular we show that this entropy definition fixes the problem inherent the exact extensivity of the caloric equation. Furthermore, this entropy reproduces results which are in agreement with the ones predicted with standard Boltzmann entropy when applied to macroscopic systems. On the contrary, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…It is not out of place to mention that the above given definition has recently been, and to some extent still is controversial, in fact it has been recently argued [ 24 ] that only the Gibbs definition of entropy yields a consistent thermodynamics, whereas this would not be the case of Boltzmann entropy. To the contrary, we have pointed out in References [ 13 , 14 , 25 ] that the Boltzmann definition of entropy actually provides a consistent thermodynamics.…”
Section: Introductionmentioning
confidence: 93%
“…It is not out of place to mention that the above given definition has recently been, and to some extent still is controversial, in fact it has been recently argued [ 24 ] that only the Gibbs definition of entropy yields a consistent thermodynamics, whereas this would not be the case of Boltzmann entropy. To the contrary, we have pointed out in References [ 13 , 14 , 25 ] that the Boltzmann definition of entropy actually provides a consistent thermodynamics.…”
Section: Introductionmentioning
confidence: 93%
“…In Ref. [1] we have proved that in the limit of a large number of degrees of freedom, the surface entropy predicts the same results as the Boltzmann entropy, included the possibility to observe negative temperatures. In the present work we show that, on the contrary, in the case of small systems these entropies can be inequivalent.…”
Section: Introductionmentioning
confidence: 78%
“…From a geometric point of view, the temperature derived from the surface entropy has an interesting interpretation: it is the average of the mean curvature of Σ E (the hypersurface H(x) = E) which is a geometric quantity. In fact, in [1] we have shown that in the case of the surface entropy it results…”
Section: Consequences Of the Surface Entropymentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding entropy definition, we have used the Boltzmann entropy instead of Gibbs since we are working in the ensemble with constant energy (i. e. a surface in the phase space). Discussions on this subject of descriptions can be followed through references [17,[22][23][24]. With the parameter values corresponding to the H 2 molecule, figure 1 shows the variation of the entropy S(U) which is a growing function of the internal energy U with an inflection point (dashed line, U c ).…”
Section: The Inflection Point For Entropymentioning
confidence: 99%